(untitled) (American Journal of Pedagogical and Educational Research, 2023)
This article discusses the experience of combating artillery intelligence forces and tools in conducting aero-artillery intelligence in modern western conflicts, artillery is one of the three oldest military units in the land, the main strike force of the modern Armed Forces, and its place in combat time.